Effect of Hoffman’s technique on flat nipple over nipple type and quality of Breast feeding among post-natal mothers - P.PONMATHI; NALAMSAI MOUNIKA; B. VIJAYALAKSHMI; V.P.R.SIVAKUMAR (International Journal of Pharma and Bio Sciences, 2017)
In women who are pregnant for the first time it is very common for the nipple to not protrude fully. Flat nipples may be difficult to baby to grasp. In order to improve the breast feeding effectively, the Hoffman’s technique is applied. Effect of Hoffman’s technique on flat nipple over nipple type and quality of breast feeding among immediate post-natal mothers – Case Report. Study type was case series, Inclusion criteria female those who are breast feeding, 45 days from delivery, primipara and multipara women, Both normal delivery and ceasarean, Age between 25 to 35 years. 2 Subjects were selected according to inclusion and exclusion criteria. Outcome measure were pinch test and breast feeding satisfaction. Incase 1, the pinch test is positive for pretest and negative for post test and the quality of breast feeding is improved after the Hoffman’s technique is applied. In Case 2, the pretest is positive and post test is negative for pinch test and due to the effect of Hoffman’s technique and the quality of breast feeding is also improved. This study concludes that Hoffman’s technique have an effect of nipple type and Quality of breast feeding and can be used among postnatal and Antenatal mothers to improve the Quality of Breast Feeding.